Is There a Place for the Endoscope in Skull Base Surgery in Children Less Than 5 Years? - Holzmann, David; Bozinov, Oliver; Krayenbühl, Niklaus (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background The impact of transnasal endoscopic approaches to the central skull is still increasing. Its use in small children (i.e., under the age of 5 years) is of questionable value.Patients and Methods The present study is a description of a series of five children under the age of 5 years with lesions of the central skull base.Results Three out of five required a combined external and transnasal endoscopic approach. The transnasal access to the central skull base allowed reducing tissue damage and potentially may reduce growth deceleration.Discussion Based on our experience on this small series we suggest that a transnasal endoscopic approach to the anterior and central skull base can be applied even in small children. To successfully operate on such delicate pathologies, a well-working interdisciplinary cooperation is mandatory.
Keywords: endoscopy; pediatric; skull base surgery